PENGARUH SERTIFIKASI HALAL DAN IZIN EDAR BPOM TERHADAP MINAT BELI KONSUMEN PRODUK KOSMETIK PADA MAHASISWI FAKULTAS AGAMA ISLAM UNISMUH MAKASSAR TAHUN 2024 - muh (LPPM STAI Muhammadiyah Probolinggo, 2025)
Awareness of the importance of halal certification and BPOM distribution permits has grown alongside increasing consumer concern for both safety and compliance with Islamic principles in cosmetic products. These two aspects often serve as key considerations in purchase decisions, especially among students who possess a strong understanding of religious values and regulatory standards. This study aims to analyze the influence of halal certification and BPOM permits on the purchase intention of female students at the Faculty of Islamic Studies, Muhammadiyah University of Makassar, in 2024. A quantitative approach was applied using multiple linear regression analysis, with data collected through questionnaires distributed to respondents selected by probability sampling. The results indicate that halal certification has a significant effect on purchase intention (t = 5.921 > t-table 1.971), as does the BPOM permit (t = 9.412 > t-table). Simultaneous testing also reveals a strong and significant effect (F = 204.125 > F-table 3.04) with a coefficient of determination (R²) of 0.579, meaning that 57.9% of the variation in purchase intention is explained by these two factors, while 42.1% is influenced by other variables. These findings highlight that halal certification enhances consumer trust and confidence, while BPOM permits ensure legality and product safety, making both critical in shaping cosmetic purchasing decisions.